2016
DOI: 10.3389/fcvm.2016.00010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Causes and Implications of Endothelial Metabolic Variation in Cardiovascular Disease through Genome-Scale Metabolic Modeling

Abstract: High-throughput biochemical profiling has led to a requirement for advanced data interpretation techniques capable of integrating the analysis of gene, protein, and metabolic profiles to shed light on genotype–phenotype relationships. Herein, we consider the current state of knowledge of endothelial cell (EC) metabolism and its connections to cardiovascular disease (CVD) and explore the use of genome-scale metabolic models (GEMs) for integrating metabolic and genomic data. GEMs combine gene expression and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 134 publications
(114 reference statements)
0
11
0
Order By: Relevance
“…As stated in the Introduction section, the action of neural, hormonal, paracrine or cytokine signaling directly or indirectly modifies cellular metabolic pathways [ 11 , 24 ]. Furthermore, it was shown that even the endothelial mechanoreceptors activity can alter circulating metabolites and may be revealed by metabolomics [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…As stated in the Introduction section, the action of neural, hormonal, paracrine or cytokine signaling directly or indirectly modifies cellular metabolic pathways [ 11 , 24 ]. Furthermore, it was shown that even the endothelial mechanoreceptors activity can alter circulating metabolites and may be revealed by metabolomics [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, genome-scale models of cancer metabolism can help us comprehend the complexity of human cancer heterogeneity in relation to substrate preference and therefore expedite the discovery of putative anticancer targets ( 285 ). Genome-scale metabolic models can also be applied to investigate genetic variation in genotype-phenotype interactions and as such can be used to identify metabolic biomarkers and discover treatments based on genetic markers ( 311 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…However, these molecular mechanisms still remain to be addressed in details. Recent findings unraveled that endothelial cell biology is driven by a metabolic switch, and metabolic alterations in endothelial cells could mediate angiogenesis and vasculature formation (Eelen et al, 2015; McGarrity et al, 2016). Additionally, as the final downstream products of transcription and translation, metabolites serve as the potential indicators of enzyme activities in pathological and pathophysiological conditions, and metabolomic assay might reveal the overall abnormal metabolic changes in CVD (Kordalewska and Markuszewski, 2015; Würtz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%